EXAMINING SUBSTANCE ABUSE AND JUVENILE DELIQUENCY WHILE DEVELOPING CULTURALLY TAILORED INTERVENTIONS FOR JAATIKARAN SEMI-NOMADIC TRIBES CHILDREN & YOUTH IN TIRUVALLUR DISTRICT, TAMIL NADU - Vinod V.S,; Dr. Karuppiah,; Akilas K Abraham,; Dr Dhannia P Narayanan,; 5Angel. S, (The Bioscan, 2025)
India shares a complex and enduring relationship with its mobile communities, often shaped by colonial stigmatization that labelled certain groups as 'criminals by birth' due to their nomadic lifestyles. In Tamil Nadu, only three communities - Jaatikaran or Sattai Adikiravar, Narikuravars, and Boomboom Maattukarar - have been officially recognized as nomadic tribes, despite the presence of approximately 68 denotified communities in the state. Within the Jaatikaran community, pervasive poverty is a defining characteristic. This economic deprivation, coupled with a dearth of opportunities for personal growth, leads most of the youth and children towards engaging in delinquent activities as a means of survival or escape. Like many other communities, peer pressure plays a significant role in shaping the behavior of the youth and children in this community. When peer groups encourage delinquent activities, it contributes to the proliferation of issues such as alcoholism, drug addiction, theft, minor crimes, and anti-social behaviour among the Jaatikaran community. Efforts are underway, led by the researcher through the Jeevan Center (YWAM- a non profit organisation), to address delinquent behaviors within the Jaatikaran tribe in Alamathy village. These initiatives include raising awareness about access to education, vocational training, and community engagement, as well as implementing culturally sensitive interventions. These endeavors are instrumental in preventing and addressing issues related to substance abuse and juvenile delinquency. This article seeks to explore the life experiences and socio- economic, cultural and environmental factors which is contributing to substance abuse and delinquent behaviours among the marginalized Jaatikaran community, also known as saatai adikiravar, residing in the ABC Colony of Alamathy village near Redhills in Tiruvallur district."